PERAN LEMBAGA PENDIDIKAN DALAM MEMERANGI BERITA HOAX: PERSPEKTIF AL-QUR’AN - Mufti, Umam; Waharjani, Waharjani (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
The role of an educational institution has a big responsibility in shaping the ethics and personality of the participants. The rapid progress of the times and sophisticated technology makes the space indefinitely which eventually leads to a variety of positive and negative impacts, its positive impact is so easy to obtain information, while the downside is many information that is not able to be answered that resulted in the understanding and developing of the news lying (hoax), the Qur'an as a source of scientific excavation has offered a concept for humans, especially students education through Islamic religious educational learning materials. The conceptualization and theorization of the Qur'an in this paper uses analysis content with steps; Unitizing, Sampling, Recording, Reducing, Inferring, Analyzing and Narrating. These methodological measures will result in an anti-hoax education concept sourced from the Qur'an and combined with several theories in favor. The results build a formulation of how to build personality for honest learners and avoid the hoaxes of Islamic education institutions.